Evidence-Based Approaches to Remedy and Also to Prevent Abuse of Community-Dwelling Older Persons - Donna M. Wilson; Sandra E. Ratajewicz; Charl Els; Mary A. Asirifi (Nursing Research and Practice)
Elder abuse is a global issue, with an estimated 4–10% of older persons in Canada abused each year. Although Canadian legislation has been created to prevent and punish the abuse of older persons living in nursing homes and other care facilities, community-dwelling older persons are at greater risk of abuse. This paper highlights the importance of evidence-based actions targeted at three determinants of health: (a) personal health practices and coping skills, (b) social support networks, and (c) social environments. Two research studies are profiled as case studies that illustrate the ready possibility and value of two specific types of actions on community-based older-person abuse. This paper argues for the immediate and widespread adoption of these evidence-based measures and for additional empirical evidence to guide the correction of underreporting of abuse, raise awareness of its serious nature, and increase options to not only stop it but ultimately prevent it.